The internal control practices of selected mosques in Java, Indonesia - Nining Islamiyah (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2021)
Internal controls are necessary tools to help organisations attain their organisational goals. Lack of these controls could lead to fraudulent activities, which may hamper the achievement of the goals. Thus, this study aims to investigate the internal control practices in two selected Indonesian mosques: Mosque A and Mosque B. The study employs the Committee of Sponsoring Organisation – Internal Control Integrated Framework (COSO, 2013) framework of internal controls to frame the investigation of internal control practices in these two mosques. Data collection was undertaken through interviews and reviews of relevant documents. The findings reveal that the two selected mosques; Mosque A and Mosque B, have five mechanisms of internal control practices in place. These include control environment, risk assessment, control activities, information and communication, and monitoring activities. The internal control practices and the operationalisation are viewed through the lens of accountability. Using the notion of accountability, the study further observed five accountability themes within these two mosques, namely the medium communication, the assessment mechanism, the importance of participatory mechanisms, self-regulation, and disclosure statements and reports. This study concludes that internal control practices are a necessary process to support the accountability operationalisation of the mosque. The results of this study may serve as a potential reference for the improvement of internal control practices in the Indonesian mosques.